THE ANALYSIS OF CLAUSE COMPLEX IN THE STUDENTS’ CASUAL CONVERSATION - Ifadloh, Nur; Nufus, Zahratun (English Department of Faculty of Tarbiyah and Teacher Training, 2017)
This study reported on an analysis of the transcript of the students? conversation. It highlighted the way in which the transcript was analyzed qualitatively on the issue of clause complexity based on the perspective of Systemic Functional Linguistics (SFL). In detail, this study demonstrated the clause complexity of the transcript of the students? conversation which was related to, for example, inter-clausal relations (logico-semantic relation), coordination (parataxis) and subordination (hypotaxis) as mainly outlined by Halliday (1994), Halliday & Matthiessen (2004) and Eggins (2004). The results of the analyses indicated that the students showed a positive trend of developments in the use of semantic relations in their conversation. The students produced clause complexes (37.71%) less than clause simplexes (62.29%), In the syntactic dimension, the students produced hypotaxis (50.65%) more than parataxis (49.35%). In hypotaxis, the students produced expansion (92.31%) more than projection (7.69%). It also occurred in parataxis where students also produced expansion (92.11%) more than projection (7.89%). In the logico-semantic dimension, students produced expansion (92.47%) more than projection (7.53%). In the case of projection, locution (57.14%) was produced more than idea (42.86%). In addition, in the case of expansion, elaboration (40.70%) was the most frequently used by the students rather than both of extension (34.88%) and enhancement (24.42%).